The meaning of biculturalism - Walker, Ranginui (R.J. Walker, 1986)
Keywords: bicultural; capitalism; colonisation; race relations; tiriti o waitangi/treaty of waitangi

Race Relations and the Treaty: A Framework for Resolution - Gardiner, Wira (Partnership and peace: essays on biculturalism in Aotearoa - New Zealand, 1990)
Keywords: government; race relations; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Maori sovereignty: the Maori perspective - Melbourne, Hineani (Hodder Moa Beckett, 1995)
Keywords: ethnic identity; government relations; mmp electoral system; race relations; rangatiratanga; social conditions; tiriti o waitangi/treaty of waitangi; treaty claims

Chapter 6: Iwi Development and the Waikato-Tainui Experience - Mahuta, Robert (Nga Patai: racism and ethnic relations in Aotearoa/New Zealand, 1996)
Keywords: development; iwi; iwi development; race relations; racism; rangatiratanga

Te hiikoi ki Waitangi: a discussion paper - Te Maru, John E. (University of Waikato, Centre for Maaori Studies and Research, 1984)
Keywords: crown; iwi; kāwanatanga; kīngitanga; race relations; rangatiratanga; raupatu; tainui; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

The changing role of the leader in Māori society: a study in social change and race relations - Winiata, Maharaia (University of Waikato, 2014)
Keywords: government; government relations; iwi politics; kāwanatanga; kōrero nehe; leadership; noho-ā-iwi; pre-colonisation; race relations; rangatira; rangatiratanga; social life and customs

Chapter 18: The Treaty of Waitangi and Recognition of Tikanga Māori - Mikaere, Ani (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land tenure; law; race relations; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi

Chapter 15: From the Sideline: Tikanga, Treaty Values and Te Papa - Tapsell, Paul (Waitangi Revisited, 2005)
Keywords: bicultural; government relations; history; land tenure; mana whenua; marae; museums; race relations; te papa museum; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty principles

The Wai 262 Claim: A Claim by Māori to Indigenous Flora and Fauna - Solomon, Maui (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty claims; treaty settlements; waitangi tribunal

Chapter 10: Feast or Famine: Customary Fisheries Management in a Contemporary Tribal Society - Tuuta, Evelyn (Waitangi Revisited, 2005)
Keywords: crown policy; environment; government relations; history; kaitiakitanga; land tenure; māori rights; race relations; rangatiratanga; resource management; tiriti o waitangi/treaty of waitangi

Chapter 11: Recovering Fagin's Ill-Gotten Gains: Settling Ngāti Kahu's Treaty of Waitangi Claims Against the Crown - Mutu, Margaret (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Orakei - Kāwharu, Hugh (Waitangi Revisited, 2005)
Keywords: government relations; hapū; history; land tenure; ngāti whatua; political action; race relations; rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua; waitangi tribunal

Chapter 6: Rangatiratanga and Social Policy - Kawharu, Merata (Waitangi Revisited, 2005)
Keywords: crown policy; education; government relations; hauora; health; history; land tenure; race relations; rangatiratanga; social policy; tiriti o waitangi/treaty of waitangi

Chapter 7: The Treaty of Waitangi and Social Well-being: Justice, Representation, and Participation - Sullivan, Ann (Waitangi Revisited, 2005)
Keywords: crown; elections; government relations; history; land tenure; local government; māori electorates; māori seats; parliament; race relations; social justice; tiriti o waitangi/treaty of waitangi; treaty principles; voting

Chapter 1: Tino Rangatiratanga - Durie, Mason (Waitangi Revisited, 2005)
Keywords: constitution; government relations; history; kotahitanga; land tenure; marae; nationhood; race relations; self-governance; tiriti o waitangi/treaty of waitangi

Chapter Four: The Treaty of Waitangi in the Postcolonial Era - Walker, Ranginui (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land march; land tenure; post-colonialism; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

The State of Māori rights - Mutu, Margaret (Huia, 2015)
The State of Maori Rights brings together a set of articles written between 1994 and 2009. It places on record the Maori view of events and issues that took place over these years, issues that have been more typically reported to the general public from a 'mainstream' media perspective. It is an important documentation of these fifteen years of New Zealand history, recording the assertion of Maori rights as the indigenous people of Aotearoa New Zealand, focusing on Maori issues and experiences and written from a Maori perspective.
Keywords: civil Rights; colonisation; crown violence; foreshore and seabed act 2004; government relations; intergenerational trauma; kāwanatanga; mana motuhake; māori electorates; māori rights; race relations; racism; te pāti māori; tiriti o waitangi/treaty of waitangi; voting; waitangi tribunal

Maori sovereignty / Donna Awatere. - Awatere Huata, Donna (Broadsheet, 1984)
Keywords: ethnic identity; race relations; racism; tino rangatiratanga

Taua nakahi nui: Maori, liquor and land loss in the 19th century - McDowell, Tiopira (AlterNative : an international journal of indigenous peoples, 2015)
This article outlines the fraudulent practices of settler traders and land agents who employed alcohol to facilitate the alienation of Maori lands, highlighting the close relationship between Maori, liquor and land loss in 19th century New Zealand. Traders and agents developed a range of strategies, forged in Britain, tempered by colonial experience and wielded with deft precision in New Zealand to defraud Maori of their lands. Government efforts to pre-empt and prevent the worst excesses of settler crime proved ineffectual, self-defeating, paternalistic and ultimately unenforceable. Maori came to regard settler practices, the successive failure of legislation to alleviate the problem, and state connections with the liquor industry to be part of a thinly veiled conspiracy to destabilize their communities and alienate their lands. While this conclusion is highly problematic, it is likely that traders and agents had witnessed or were aware of similar practices in the settler colonies of Australia, Canada and North America, and made good use of them in New Zealand to access Maori lands.
Keywords: alcohol; colonies; crown policy; government relations; land loss; land tenure; race relations

Beyond biculturalism: the politics of an indigenous minority - O'Sullivan, Dominic (Huia, 2007)
"Beyond Biculturalism is a critical analysis of contemporary Maori public policy. Bicultural political theory dominated Maori/Crown relationships during the 1980s and 1990s and O'Sullivan argues that biculturalism inevitably makes Maori the junior partner in a colonial relationship that obstructs Maori aspirations to self-determination. The politics of indigeneity and self-determination are discussed as alternative political ideas for thinking about Maori relationships with the state. Against this background, and by drawing on Australian and Canadian comparisons, the book examines contemporary Maori political issues such as the Foreshore and Seabed Act 2004, Maori parliamentary representation, the 'one law for all' ideology, settlements of Maori grievances against the Crown, and Maori economic development."–BOOK JACKET.
Keywords: bicultural; crown policy; ethnic identity; government relations; iwi taketake; kāwanatanga; race relations; rangatiratanga; tāngata whenua